Effects of Inundation, Nutrient Availability and Plant Species Diversity on Fine Root Mass and Morphology Across a Saltmarsh Flooding Gradient - Redelstein, Regine; Dinter, Thomas; Hertel, Dietrich; Leuschner, Christoph (Frontiers in Plant Science, 2018)
Saltmarsh plants are exposed to multiple stresses including tidal inundation, salinity, wave action and sediment anoxia, which require specific root system adaptations to secure sufficient resource capture and firm anchorage in a temporary toxic environment. It is well known that many saltmarsh species develop large below-ground biomass (roots and rhizomes) but relations between fine roots, in particular, and the abiotic conditions in salt marshes are widely unknown. We studied fine root mass (< 2 mm in diameter), fine root depth distribution and fine root morphology in three typical communities (Spartina anglica-dominated pioneer zone, Atriplex portulacoides-dominated lower marsh, Elytrigia atherica-dominated upper marsh) across elevational gradients in two tidal salt marshes of the German North Sea coast (a mostly sandy marsh on a barrier island (Spiekeroog), and a silty-clayey marsh on the mainland coast (Westerhever)). Fine root mass (0-40 cm profile) ranged between 750 and 2500 g m-2 in all plots with maxima at both sites in the lower marsh with intermediate inundation frequency and highest plant species richness indicating an effect of biodiversity on fine root mass. Fine root mass and, even more, total fine root surface area (maximum 340 m2 m 2) were high compared to terrestrial grasslands, and were greater in the nutrient-poorer Spiekeroog marsh. Fine root density showed only a slight or no decrease towards 40 cm depth. We conclude that the standing fine root mass and morphology of these salt marshes is mainly under control of species identity and nutrient availability, but species richness is especially influential. The plants of the pioneer zone and lower marsh are able to possess well adapted fine roots and large standing root masses despite the often water-saturated sediment.